Squamous Cell Carcinoma - Rao Rashad Qamar, Mazhar-U-Zaman Soomro (Pakistan Journal of Ophthalmology, 2006)
38 years old young man presented with mass on the temporal side of cornea in the interpelpebral fissure area with symptom of only irritation in the right eye. On excision biopsy, mass turned out to be squamous cell carcinoma of the conjunctiva.